Response of freshwater diatoms to cold events in the Late Pleistocene and Early Holocene (SE Baltic region). (10th July 2021) - Spiridonov, Andrej; Vaikutienė, Giedrė; Stankevič, Robertas; Druzhinina, Olga; Šeirienė, Vaida; Subetto, Dmitry; Kublitsky, Jury; Stančikaitė, Miglė
Abstract: The Late Pleistocene and Early Holocene were time periods of significant transitions between glacial and warm climate states. In this contribution, a study of changes of diatom assemblage compositions in recurrence plots, rarefaction models, and their rank abundance distributions (Fisher's alpha) in the Southeast Baltic is presented. Three sites were studied for this purpose: Lake Kamyshovoye (Kaliningrad Region, Russia), Lake Kašučiai (W Lithuania), and Lake Petrešiūnai (NE Lithuania). The recurrence plots revealed a compositionally stable interval at the end of the Pleistocene and a subsequent continuous and directional turnover (compositional trend) of local diatom communities throughout the Early Holocene. An analysis of rank abundance distributions and rarefaction analysis revealed a persistent long-term increase in the diversity of diatoms which started after the Younger Dryas cold episode; additional data suggest possible effects of the multi-centennial scale "9.3" Ka BP cold event. The close correlation between diatom diversity changes and geographically widespread climatic trends shows strong potential for this algae group in the regional analyses of climatic perturbations.